2016
DOI: 10.7324/jabb.2016.40501
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and ß-amino butyric acid up-regulates transcripts of resistance gene analog RGPM213 in pearl millet to infection by downy mildew pathogen

Abstract: Plants are hosts to a diverse group of pathogens belonging to different kingdoms of life. In absence of active immune system, plants have evolved several layers of defense to combat individual pathogen strain and evolving pathogen populations. Management of various plant pathogen infections necessitates the use of multiple resistance (R) genes, which requires efficient and accurate practices for identification, isolation and characterization of R genes. This knowledge helps to probe R gene(s) in a host plant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Tests carried out in both greenhouse and field conditions on pearl millet showed that chitosan seed priming protects crops from downy mildew. Furthermore, the effect of chitosan on the regulation of resistance gene analogue RGPM213 to infection by downy mildew pathogen was also investigated in pearl millet [141]. The use of this substance causes systemic and durable resistance to this type of infection [58,142,143].…”
Section: Pathogen and Disease Controlmentioning
confidence: 99%
“…Tests carried out in both greenhouse and field conditions on pearl millet showed that chitosan seed priming protects crops from downy mildew. Furthermore, the effect of chitosan on the regulation of resistance gene analogue RGPM213 to infection by downy mildew pathogen was also investigated in pearl millet [141]. The use of this substance causes systemic and durable resistance to this type of infection [58,142,143].…”
Section: Pathogen and Disease Controlmentioning
confidence: 99%